Manual of sheep diseases. - Hindson, J.C; Winter, Agnes C.
"This revised and updated version of Outline of Clinical Diagnosis in Sheep now covers the whole field of diagnosis, treatment and prevention of diseases and poor production of sheep. It is aimed a the non-specialists veterinarian and fills a niche between the large, comprehensive books on sheep and the shorter texts aimed at farmers. It will also appeal to all those involved in sheep production, and is a valuable reference for veterinary students. A wide range of diseases and conditions is covered, together with important aspects of production such as lamb output and growth rates. New sections have been added on nutrition (which has a significant effect on all aspects of production), anaesthesia, vaccination programmes, and parasite control"--